2015
DOI: 10.1002/2014ja020497
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray imaging of Kelvin‐Helmholtz waves at the magnetopause

Abstract: This paper simulates the Kelvin‐Helmholtz wave (KHW)‐induced X‐ray emissions at the low‐latitude magnetopause based on a global MHD code. A method is proposed to extract the KHW information from the X‐ray intensity measured by a hypothetical X‐ray telescope onboard a satellite assumed with a low Earth orbit. Specifically, the X‐ray intensity at high latitude is subtracted from the intensity map as a background to highlight the role of KHW. Using this method, global features of KHW such as the vortex velocity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The model we use to calculate the X‐ray intensity along a given direction ( I X ) is similar to that described by Sun et al (), which is the line integration of the X‐ray emissivity P X : IX=14πPXnormaldr=14παXnHnswgnormaldr2.56804pt2.56804pt2.56804ptfalse(keV.1em·.1emcm2·s1·sr1false), …”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model we use to calculate the X‐ray intensity along a given direction ( I X ) is similar to that described by Sun et al (), which is the line integration of the X‐ray emissivity P X : IX=14πPXnormaldr=14παXnHnswgnormaldr2.56804pt2.56804pt2.56804ptfalse(keV.1em·.1emcm2·s1·sr1false), …”
Section: Model Descriptionmentioning
confidence: 99%
“…Connor and Carter () selected a case of an XMM‐Newton observation and compared the simulation result with observation in order to estimate the exospheric neutral density. Transient structures on the magnetopause such as flux transfer events and Kelvin‐Helmholtz waves were also investigated numerically (Collier et al, ; Sun et al, ). Despite these studies, there are still some basic issues not sufficiently analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Although they concluded that integrated line-of-sight charge exchange soft X-ray intensities are less than those of the soft X-ray background during quiet times, they can rise to values far greater than those of the soft X-ray background during intervals of enhanced solar wind plasma fluxes. Sun et al (2015) employed the 3-D PPMLR global MHD plasma model (Hu et al 2007) and a simple exospheric neutral model to define the soft X-ray signatures that would be observed by an outward-looking low-altitude spacecraft when Kelvin-Helmholtz waves move antisunward on the flanks of the magnetosphere. They showed how the amplitude, speed, distribution, and temporal evolution of the vortices can be derived from the simulated soft Based on values reported for ROSAT observations through the flank magnetosheath .…”
Section: Relative Emission Strengthsmentioning
confidence: 99%
“…This tool could be used to study a variety of processes. Other modeling efforts have suggested transient phenomena such as flux transfer events, and Kelvin-Helmholtz waves may also be observable through soft X-ray imaging [Sun et al, 2015].…”
Section: 1002/2016ja022348mentioning
confidence: 99%